Influence of Exercise Order in a Resistance‐Training Exercise Session - Spreuwenberg, Luuk P.B.; Kraemer, William J.; Spiering, Barry A.; Volek, Jeff S.; Hatfield, Disa L.; Silvestre, Ricardo; Vingren, Jakob L.; Fragala, Maren S.; Häkkinen, Keijo; Newton, Robert U.; Maresh, Carl M.; Fleck, Steven J. (Journal of strength and conditioning research, 2006)
The order of resistance exercises within a training session may have a vital impact on the quality of the constituent exercises performed. However, very few studies have documented the specific influence of exercise order. Therefore, the purpose of this study was to examine the effect of exercise order on back squat performance in the context of a whole-body workout. Nine resistance-trained male subjects (age: 24 plus or minus 4 years, body mass: 81.5 plus or minus 15.3 kg, resistance-training experience: 7 plus or minus 4 years) performed the back squat exercise (4 sets at 85% of 1 repetition maximum) on 2 separate occasions in a balanced, crossover design. During one protocol, the squat exercise was performed first (protocol A); during the other protocol, it was performed after a whole-body resistance-exercise session (protocol B). Number of repetitions, average power, and rating of perceived exertion (RPE) were collected during each set of the squat exercise.